Physically Based Modeling of Delta Island Consumptive Use: Fabian Tract and Staten Island, California - Lucas J. Siegfried; William E. Fleenor; Jay R. Lund (eScholarship Publishing, University of California, 2014)
doi: http://dx.doi.org/10.15447/sfews.2014v12iss4art2Water use estimation is central to managing most water problems. To better understand water use in California’s Sacramento–San Joaquin Delta, a collaborative, integrated approach was used to predict Delta island diversion, consumption, and return of water on a more detailed temporal and spatial resolution. Fabian Tract and Staten Island were selected for this pilot study based on available data and island accessibility. Historical diversion and return location data, water rights claims, LiDAR digital elevation model data, and Google Earth were used to predict island diversion and return locations, which were tested and improved through ground-truthing. Soil and land-use characteristics as well as weather data were incorporated with the Integrated Water Flow Model Demand Calculator to estimate water use and runoff returns from input agricultural lands. For modeling, the islands were divided into grid cells forming subregions, representing fields, levees, ditches, and roads. The subregions were joined hydrographically to form diversion and return watersheds related to return and diversion locations. Diversions and returns were limited by physical capacities. Differences between initial model and measured results point to the importance of seepage into deeply subsided islands. The capabilities of the models presented far exceeded current knowledge of agricultural practices within the Delta, demonstrating the need for more data collection to enable improvements upon current Delta Island Consumptive Use estimates.